Utility of Analgesic and Anxiolytic Medication Dose during Colonoscopy in Identifying Patients with Irritable Bowel Syndrome. (4th January 2012) - Lule, Enoch; Iddings, Erika; Manandhar, Lochana; Grandhi, Bala; Clements, John
Abstract : Research question . This paper was done to answer the question on whether patients with IBS require higher analgesic or anxiolytic doses during colonoscopy. Setting . Gastroenterology practice in Michigan, USA. Methods . We reviewed the charts of patients following up with a US based gastroenterology practice. We collected data on whether or not they had IBS, and collected data on analgesic and anxiolytic requirement during colonoscopy. Results . 336 patients were included in the trial. 206 did not have IBS while 130 had a previous diagnosis of IBS. 234 were female (67.2%). When comparing patients who have IBS to those without IBS, we identified no statistically significant difference in midazolam dose (5.5 mg versus 5.5 mg), fentanyl dose ( 117 mg versus 112 mg) or meperidine dose (69 mg versus 69 mg). The lack of differences in medication doses used remained when we controlled for sex, prior analgesic use, and prior abdominal surgery. Conclusion . Dose of analgesic or anxiolytic used during colonoscopy cannot be used to identify patients with IBS.